The Relationship Between Improvements in Myelopathy and Sagittal Realignment in Cervical Deformity Surgery Outcomes. Issue 16 (August 2018) - Passias, Peter Gust; Horn, Samantha R.; Bortz, Cole A.; Ramachandran, Subaraman; Burton, Douglas C.; Protopsaltis, Themistocles; Lafage, Renaud; Lafage, Virginie; Diebo, Bassel G.; Poorman, Gregory W.; Segreto, Frank A.; Smith, Justin S.; et al.
Abstract : Study Design: Retrospective review. Objective: Determine whether alignment or myelopathy improvement drives patient outcomes after cervical deformity (CD) corrective surgery. Summary of Background Data: CD correction involves radiographic malalignment correction and procedures to improve motor function and pain. It is unknown whether alignment or myelopathy improvement drives patient outcomes. Methods: Inclusion: Patients with CD with baseline/1-year radiographic and outcome scores. Cervical alignment improvement was defined by improvement in Ames CD modifiers. modified Japanese Orthopaedic Association (mJOA) improvement was defined as mild [15–17], moderate [12–14], severe [<12]. Patient groups included those who only improved in alignment, those who only improved in mJOA, those who improved in both, and those who did not improve. Changes in quality-of-life scores (neck disability index [NDI], EuroQuol-5 dimensions [EQ-5D], mJOA) were evaluated between groups. Results: A total of 70 patients (62 yr, 51% F) were included. Overall preoperative mJOA score was 13.04 ± 2.35. At baseline, 21 (30%) patients had mild myelopathy, 33 (47%) moderate, and 16 (23%) severe. Out of 70 patients 30 (44%) improved in mJOA and 13 (18.6%) met 1-year mJOA minimal clinically important difference. Distribution of improvement groups: 16/70 (23%) alignment-only improvement, 13 (19%) myelopathy-only improvement, 18 (26%) alignment and myelopathy improvement, and 23 (33%) no improvement. EQ-5D improved in 11 of 16 (69%) alignment-only patients, 11 of 18 (61%) myelopathy/alignment improvement, 13 of 13 (100%) myelopathy-only, and 10 of 23 (44%) no myelopathy/alignment improvement. There were no differences in decompression, baseline alignment, mJOA, EQ-5D, or NDI between groups. Patients who improved only in myelopathy showed significant differences in baseline-1Y EQ-5D (baseline: 0.74, 1 yr:0.83, P  < 0.001). One-year C2-S1 sagittal vertical axis (SVA; mJOA r  = −0.424, P  = 0.002; EQ-5D r  = −0.261, P  = 0.050; NDI r  = 0.321, P  = 0.015) and C7-S1 SVA (mJOA r  = −0.494, P  < 0.001; EQ-5D r  = −0.284, P  = 0.031; NDI r  = 0.334, P  = 0.010) were correlated with improvement in health-related qualities of life. Conclusion: After CD-corrective surgery, improvements in myelopathy symptoms and functional score were associated with superior 1-year patient-reported outcomes. Although there were no relationships between cervical-specific sagittal parameters and patient outcomes, global parameters of C2-S1 SVA and C7-S1 SVA showed significant correlations with overall 1-year mJOA, EQ-5D, and NDI. These results highlight myelopathy improvement as a key driver of patient-reported outcomes, and confirm the importance of sagittal alignment in patients with CD. Level of Evidence: 3